Peran masyarakat dalam pengelolaan sampah impor - Septianingrum, Dinni; Sagala, Donar; Khairunisa; Saleh, Raisha Larasati (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Waste management has currently become a significant problem faced by every segment of society, from individuals to institutions. It is almost certain that the amount of waste will increase each year due to Indonesia's large population. According to data from the Ministry of Environment, the general waste generated is approximately 2.5 liters per person per day or equivalent to a total of 625 million liters. The method used in writing this article is a qualitative approach through literature review or literature study. The literature used in this writing consists of scientific articles relevant to the discussion of imported waste. Since 2018, the Chinese government has successfully reduced the level of plastic waste imports due to policies restricting waste imports. This has led waste-exporting countries to seek new target markets, especially in Southeast Asia. The issue of waste imports in Indonesia persists despite existing bans, as there is still imported waste used as a source of livelihood for the community. Importing waste has environmental and environmental pollution crises and negative impacts on human health due to water and air pollution caused by imported waste management. Regulations regarding the ban on waste imports will be effective with the involvement of the community, starting with knowledge about waste, waste management, and its dangers. The role of the community in the recycling process is crucial to reduce the burden of waste collection, industrial and hazardous waste, mitigate environmental impacts, and increase income.